Profitability of Icelandic Hotels - Rúnar Guðnason 1978- (2013)
The main objective of this research was to find out why hotel profitability in Iceland has been low and how it can be improved. Many possible explanations have been proposed in this context but no inquiry has been conducted into the factors that might explain the low profitability in the Icelandic hotel industry and indicate how it might be improved. Factors affecting firm profitability are numerous and originate both externally from the surrounding economy or industry and from within the firm. To know to which degree each of these drivers influence the bottom line can be of great value for the Icelandic hotel industry, as the remedies are different. Data for 54 for Icelandic hotels from 2007-2011 was collected. The effects of changes in the state of the economy, effects from factors that shape the industry and the impact of internal factors on hotel return are examined via panel regression test. Test results show that hotel location, changes in the real exchange rate, financial leverage ratio, changes in hotel room demand and operating efficiency are significant explanatory factors of hotel returns. The main findings of the study are that interaction between changes in the real exchange rate and over leverage were probably the main reasons for low hotel profitability over the period from 2007 to 2011. To improve profitability, hotel operators should focus more on improving the internal factors of the business rather than focusing on the external factors. Keywords: hotel profitability, economic factors, industry factors, business-specific factors.